The South China Sea Dispute Philippine Sovereign Rights and Jurisdiction in the West Philippine Sea (Philippine Law Journal, 2017)
The root cause of the South China Sea dispute is the map containing the nine-dashed line submitted by China to the United Nations in 2009. In 2013, the Philippines submitted an arbitration case against China to rule on the extent of maritime entitlements of certain land features, regardless of what state exercises sovereignty over them. The case involved an interpretation of the United Nations Convention on the Law of the Sea (UNCLOS) provisions on maritime entitlements, and did not involve delimitation of overlapping seas, exclusive economic zones (EEZs), or continental shelves between or among coastal states. In July 2016, the arbitral tribunal constituted under Annex VII of the UNCLOS ruled against China's nine-clashed line claim. This work details the interactions between the Philippines and China in the years leading up to the arbitration case. It also examines the issues raised by the Philippines in the arbitration case and the resolutions presented by the arbitral tribunal. Proposals for enforcement mechanisms and peaceful courses of action honoring the Philippine claim, as well as those of its neighbors, arc also presented.